2013
DOI: 10.2105/ajph.2012.301209
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Universal Preventive Intervention on Prescription Drug Misuse: Three Randomized Controlled Trials With Late Adolescents and Young Adults

Abstract: Objectives Examine long-term prescription drug misuse outcomes from three RCTs of brief universal preventive interventions conducted during middle school. Methods Study 1 tested the Iowa Strengthening Families Program (ISFP); 22 schools participated, with pretesting at grade 6 (1993) and outcomes measured at age 25. Study 2 evaluated a revised ISFP, renamed Strengthening Families Program: For Parents and Youth 10–14—SFP 10–14, plus the school-based Life Skills Training (SFP 10–14 + LST); 24 schools participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 34 publications
3
84
0
1
Order By: Relevance
“…Second, individuals aged 18 to 25 were more likely than most other groups to possess pain reliever from friends/relatives or through purchase from a drug dealer/stranger. These findings offer further evidence towards interventions intended to communication and awareness among families about the negative consequences of distributing prescription painrelievers to others (Spoth, Trudeau, Shin, et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…Second, individuals aged 18 to 25 were more likely than most other groups to possess pain reliever from friends/relatives or through purchase from a drug dealer/stranger. These findings offer further evidence towards interventions intended to communication and awareness among families about the negative consequences of distributing prescription painrelievers to others (Spoth, Trudeau, Shin, et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…Some of the variation in findings could be because demographics and broad risk factors are proxies for other factors that explain more of the variation in findings. Spoth et al (2013) proposed the Translation Science to Population Impact Framework (TSci Impact Framework) that illuminated the critical importance of examining the creation and implementation of evidence-based interventions at all phases, for different populations, and at all levels of the system. Aligned with this framework is the idea discussed in this paper to examine participant engagement with a similar systems lens.…”
Section: Challenges Of Participant Engagement and Retention In Prevenmentioning
confidence: 99%
“…The recommendations below align with the TSci Impact Framework including the connections between research and practice, the use of innovative designs, the inclusion of potential participants (and providers) in the earliest phases of development, and consumer or market analysis to examine both preferences and barriers for evidence-based interventions in communities to be successful and sustained (Spoth et al 2013). …”
Section: Considerations For the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that those who attended the educational session were 1.8 times more likely to be discharged due to violation of the treatment agreement, and the explanation was that participants in the educational session could perceive a false sense of privilege becaus they had participated in their care beyond a typical first physician office visit. 90 Sixteen strategies had no effect on this outcome, 31,33,35,37,38,47,52,59,61,66,71,73,75,83,86,89 10 strategies had a small positive effect, 37,38,56,62,65,77,78,85,87,92 six strategies (seven studies) had a moderate positive effect, 34,40,44,58,80,95,97 and seven had a large positive effect, which included (1) a standard protocol for buprenorphine with naloxone for patients with low- The aim of study was to demonstrate noninferiority rather than superiority of the intervention.…”
mentioning
confidence: 99%